Social media marketing strategy in English football clubs - McCarthy, J.; Rowley, J.; Keegan, B. J. (Soccer & Society, 2022)
The aim of this study is to explore the evolving social media marketing strategies of football clubs involved in the English Premier League (EPL), in a constantly changing sporting and digital landscape. Interviews conducted with practitioners from a range of clubs revealed that social media marketing has been fully adopted as a key strategic marketing channel. Other insights include the importance of trust to clubs being able to harness the collective of passionate fans on social media platforms. Also, how clubs are using social media to grow their global reach and capitalize on worldwide EPL exposure. The paper also highlights some of the negatives of social media, as experienced by football club social media marketing practitioners. Finally, a social media marketing strategy framework applied to football is proposed, based on the social media marketing strategy of football clubs and their understanding of why and how their fans use social media.